DYNAMIQUE DE LA VEGETATION ET FREQUENCE DES FEUX DE BROUSSE DANS LA RESERVE DE FAUNE D’ABOKOUAMEKRO (CENTRE, COTE D’IVOIRE) - Kouakou Bob, Kouadio; Hypollite, N’Da Dibi; Aimé, Vroh Bi Tra; Casimir, Zobi Irié; Edouard, N’Guessan Kouakou (European Scientific Journal, ESJ, 2013)
In Côte d’Ivoire, the use of repeated and anarchistic bushfires creates damages on the ecosystem, and constitutes an alarming issue for protected areas managers. This study aims to enhance knowledges on the vegetation, by evaluating their floristic potential and their relationship with some environmental factors, in the wildlife Reserve of Abokouamékro. To reach those objectives, floristic and structural characteristics of gallery forests, island forests, woodland savannas and shrubs, burned by different frequency of bushfires were compared, after a floristic inventory. The results showed that 321 species belonging to 220 genera and 77 families had been recorded in the wildlife Reserve of Abokouamékro. Also, despite the type of vegetation, when the fires frequency is higher, the various types of végétation of the reserve are converted into savannas by decreasing the number, the diversity and the basal area of the species. In order to do a better conservation and a sustainable management of this reserve, a particular attention must be observed for its protection from bushfires.